In vivo Imaging With 18F-FDG- and 18F-Florbetaben-PET/MRI Detects Pathological Changes in the Brain of the Commonly Used 5XFAD Mouse Model of Alzheimer's Disease - Franke, Timon N.; Irwin, Caroline; Bayer, Thomas A.; Brenner, Winfried; Beindorff, Nicola; Bouter, Caroline; Bouter, Yvonne (Frontiers in Medicine, 2020)
Imaging biomarkers of Alzheimer’s disease (AD) that are able to detect molecular changes in vivo and transgenic animal models mimicking AD pathologies are essential for the evaluation of new therapeutic strategies. Positron-emission tomography (PET) using either 18F-Fluorodeoxyglucose (18F-FDG) or amyloid-tracers is a well-established, non-invasive tool in the clinical diagnostics of AD assessing two major pathological hallmarks. 18F-FDG-PET is able to detect early changes in cerebral glucose metabolism and amyloid-PET shows cerebral amyloid load. However, the suitability of 18F-FDG- and amyloid-PET in the widely used 5XFAD mouse model of AD is unclear as only a few studies on the use of PET biomarkers are available showing some conflicting results. The aim of this study was the evaluation of 18F-FDG-PET and amyloid-PET in 5XFAD mice in comparison to neurological deficits and neuropathological changes. 7- and 12-months-old male 5XFAD mice showed a significant reduction in brain glucose metabolism in 18F-FDG-PET and amyloid-PET with 18F-Florbetaben demonstrated an increased cerebral amyloid deposition (n=4-6 per group). Deficits in spatial reference memory were detected in 12-months-old 5XFAD mice in the Morris Water Maze (n=10-12 per group). Furthermore, an increased plaque load and gliosis could be proven immunohistochemically in 5XFAD mice (n=4-6 per group). PET biomarkers 18F-FDG and 18F-Florbetaben detected cerebral hypometabolism and increased plaque load even before the onset of severe memory deficits. Therefore, the 5XFAD mouse model of AD is well-suited for in vivo monitoring of AD pathologies and longitudinal testing of new therapeutic approaches.